2008
DOI: 10.1027/0044-3409.216.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Adaptive Testing of Personality Traits

Abstract: A computerized adaptive testing (CAT) procedure was simulated with ordinal polytomous personality data collected using a conventional paper-and-pencil testing format. An adapted Dutch version of the dominance scale of Gough and Heilbrun’s Adjective Check List (ACL) was used. This version contained Likert response scales with five categories. Item parameters were estimated using Samejima’s graded response model from the responses of 1,925 subjects. The CAT procedure was simulated using the responses of 1,517 ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…Personality assessments nowadays have not integrated CAT methodology as widely or deeply as modern cognitive ability tests, but the prospect is promising. For example, Hol, Vorst and Mellenbergh (2008) conducted a realdata simulation study using SS personality items, and found that CAT only requires as few as 33% of the original items to reach similar levels of measurement accuracy.…”
Section: Context In Forced-choice Assessmentsmentioning
confidence: 99%
“…Personality assessments nowadays have not integrated CAT methodology as widely or deeply as modern cognitive ability tests, but the prospect is promising. For example, Hol, Vorst and Mellenbergh (2008) conducted a realdata simulation study using SS personality items, and found that CAT only requires as few as 33% of the original items to reach similar levels of measurement accuracy.…”
Section: Context In Forced-choice Assessmentsmentioning
confidence: 99%
“…Advances in computer technology and the Rasch model provide possible alternatives in test development including the use of computer-adaptive testing (CAT) [8]. CAT uses an item bank stored in the computer.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, CAT selects only questions that are appropriate to the test taker's ability level based on previous responses [11]. In this way, the same number of questions can yield a more precise estimation of cognitive ability in CAT than in a conventional paper and pencil test [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to IRT, another area of test development that is receiving attention is Computer Adaptive Testing (CAT; Forbey, Ben-Porath, 2007;Hol, Vorst, Mellenbergh, 2008). With the majority of personality tests being administered online and over the computer, researchers have begun studying the benefits of CAT for personality scales.…”
Section: Computer Adaptivementioning
confidence: 99%
“…This is perhaps the greatest benefit to CAT -the ability to make more refined measurements. Not only can CAT offer more refined measurement, it can considerably shorten the time of test administration (Hol et al, 2008), which in turn may limit fatigue effects, boredom, and careless responding. It seems that the use of CAT for moral orientation research would be particularly helpful, because the scenario-based nature of these assessments would benefit from a shorter administration time.…”
Section: Computer Adaptivementioning
confidence: 99%